In Search of Social Justice: Current Developments in Higher Education and the Labour Market in Bulgaria - Ilieva-Trichkova, Petya Ivanova (My University, 2015)
The discussions about social justice date from ancient times, but despite the enduring interest in the topic and the progress made, we are still witnessing injustices throughout the world. Thus, the search for social justice, under some form, is an inseparable part of our lives. In general, social justice may be considered as a critical idea that challenges us to reform our institutions and practices in the name of greater fairness (Miller 1999, p. x). In political and policy debates, social justice is often related to fair access (Brown, 2013) but at the same time its meanings seem to vary when we consider different definitions, perspectives and social theories (Zajda, Majhanovich, & Rust, 2006). When seen in the context of higher education, social justice appears in relevant literature as a buzzword (Patton, Shahjahan, Riyad, & Osei-Kofi, 2010). Within the recent studies of higher education and public debates related to the development of higher education, more emphasis is placed on the link between higher education and the economic growth and how higher education could be more responsive to the labour market demands, and little emphasis has been put on social justice. Given this, the present study attempts to at least partially fill the gap with regard to this apparently very topical issue, especially in the context of the unprecedented worldwide expansion of higher education in the last century (Schofer & Meyer, 2005), an expansion that is expected to continue in the next decades. More specifically, the expansion of higher education intensified in the second part of the 20th century, especially after World War II. It was seen as a result of the intertwined dynamics related to demographic, economic and political pressures (Goastellec, 2008a). This trend undoubtedly contributed to the increase of the size of the student body. To illustrate this trend, we may point out that in the period between 2000 and 2007, the number of tertiary students in the world increased from 98,303,539 to 150,656,459 (UNESCO, 2009, p. 205). This growth occurred in all regions of the world, including Central and Eastern Europe, North America and Western Europe, and contributed to raising the number of tertiary graduates. Thus, in the period between 2000 and 2008, the total number of tertiary graduates in the European Union (EU) 27 increased by a total of 35 percent (or 4.5 percent per year). However, this growth was very uneven, ranging from 21.1 percent in Romania to 0.7 percent in Hungary (European Commission working staff document, 2011). The increase of the number of students and graduates was seen as enhancing the social justice in higher education, since it is assumed that expansion “extends a valued good to a broader spectrum of the population” (Arum, Gamoran, & Shavit, 2007, p. 29). However, concerns for a deep contradiction for 21st-century higher education also emerged with regard to its expansion.
Keywords: social justice; capabilities approach; John Rawls; Amartya Sen; Martha Nussbaum; higher education; access; Bulgaria; Bulgarian higher education; study to work trajectories; employment; graduate employment; Bulgarian universities; students and graduates